Mixing Public and Private Agri-Environment Schemes: Effects on Farmers Participation in Quebec, Canada - Alejandra Zaga-Mendez; Vijay Kolinjivadi; Jean-François Bissonnette; Jerome Dupras (International Journal of the Commons, 2020)
Incentive-based mechanisms, such as payments for ecosystem services (PES) are increasingly being employed to encourage adoption of biodiversity conservation practices in agriculture. Farmers’ participation in a PES depends – amongst other factors – on their interactions with previous programs and schemes. This research analyses how the institutional characteristics and interactions of incentive-based mechanisms shape the type of farmers’ participation and the achievement of desired socio-ecological outcomes. This research focusses on the institutional frameworks of two programs in the Province of Quebec, Canada: the ‘Prime-Vert’ Program (public agri-environment scheme) and the ‘Alternative Land Use Services’ (ALUS) initiative (a privately-funded “PES” scheme). The institutional prescriptions of these two programs were examined and compared through the lenses of the Institutional Analysis and Development framework. We reveal the impact of the institutional framework on farmers’ participation by assessing the degree of farmers’ engagement in the implementation and management of schemes. Our results showed a strong dependence of the private PES on the public scheme, rendering both programs ultimately managed under the remit of the provincial government. While the complementarity of both programs diversifies sources of funding for farmers, the presence of rigid rules governing these incentives tend to treat farmers as passive beneficiaries of a network of centralized subsidies which they have little control over. This compromises farmers’ autonomy as the rigidity of rules impedes any attempt to achieve active participation in the design and implementation of agri-environmental practices.